A framework to assist email users in the identification of phishing attacks. (12th October 2015) - Lötter, André; Futcher, Lynn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a framework to address the problem that email users are not well-informed or assisted by their email clients in identifying possible phishing attacks, thereby putting their personal information at risk. This paper therefore addresses the human weakness (i.e. the user's lack of knowledge of phishing attacks which causes them to fall victim to such attacks) as well as the software related issue of email clients not visually assisting and guiding the users through the user interface. Design/methodology/approach – A literature study was conducted in the main field of information security with a specific focus on understanding phishing attacks and a modelling technique was used to represent the proposed framework. This paper argues that the framework can be suitably implemented for email clients to raise awareness about phishing attacks. To validate the framework as a plausible mechanism, it was reviewed by a focus group within the School of Information and Communication Technology (ICT) at the Nelson Mandela Metropolitan University (NMMU). The focus group consisted of academics and research students in the field of information security. Findings – This paper argues that email clients should make use of feedback mechanisms to present security related aspects to their users, so as to make them aware of the characteristics pertaining to phishing attacks. To support this argument, it presents a framework to assist email users in the identification of phishing attacks. Research limitations/implications – Future research would yield interesting results if the proposed framework were implemented into an existing email client to determine the effect of the framework on the user's level of awareness of phishing attacks. Furthermore, the list of characteristics could be expanded to include all phishing types (such as clone phishing, smishing, vishing and pharming). This would make the framework more dynamic in that it could then address all forms of phishing attacks. Practical implications – The proposed framework could enable email clients to provide assistance through the user interface. Visibly relaying the security level to the users of the email client, and providing short descriptions as to why a certain email is considered suspicious, could result in raising the awareness of the average email user with regard to phishing attacks. Originality/value – This research presents a framework that email clients can use to identify common forms of normal and spear phishing attacks. The proposed framework addresses the problem that the average Internet user lacks a baseline level of online security awareness. It argues that the email client is the ideal place to raise the awareness of users regarding phishing attacks.